A New Path to Accurate Risk Adjustment: Applying CreVaR for Better Financial Reporting under IFRS 17 - Cherlyn, Cherlyn; Susyanto, Nanang (Diponegoro University, 2024)
IFRS 17 is an international financial reporting standard that emphasizes the principles of consistency, transparency, and comparability. It divides reserve recording into Present Value of Future Cash Flows (PVFCF), Risk Adjustment (RA), and Contractual Service Margin (CSM). As IFRS 17 does not prescribe a specific calculation method, companies have the flexibility to define their own risk assessment approaches. Value-at-Risk (VaR) is widely used due to its simplicity and ease of application. However, its limitations in handling large datasets can lead to reduced accuracy. Moreover, variations in methods across companies can compromise the comparability of financial standards. This study proposes an enhanced VaR calculation based on credibility theory—Credible Value-at-Risk (CreVaR)—to improve accuracy and promote greater consistency across corporate entities. The Diebold-Mariano (DM) test demonstrates that CreVaR provides a more accurate estimation of RA without overestimation, making it a suitable alternative for calculating RA under IFRS 17